Organizational readiness to implement a care model in primary care for frail older adults living at home in Sweden - Thomas, Kristin; Dannapfel, Petra (Frontiers in Health Services, 2022)
Background: The demographic change of an aging population constitutes a challenge for primary care organizations worldwide. The systematic implementation of preventative and proactive care models is needed to cope with increased care demands. Objective: To investigate the organizational readiness in primary care to implement a new care model to prevent hospitalization among frail older adults. Method: Individual qualitative interviews with health care staff investigated organizational readiness at seven primary care units in Sweden. A semi-structured interview guide was used during the interviews and included broad questions on individual and collective readiness to change. Directed content analysis and organizational readiness to change theory were used in data analysis. Results: Positive beliefs among staff such as perceived benefits and compatibility with existing values contributed to a strong commitment to implement the new care model. However, perceptions such as unclear task demands, limited resources and concerns about new collaborative structures challenged implementation. Conclusions: The findings emphasize implementation as an inter-organizational phenomenon, especially for holistic practices that span across multiple health care providers and disciplines. Furthermore, implementing care models in healthcare may require a change of culture as much as a change of practice.